The Effects of Using a Conditioned Stimulus to Cue DRO Schedules1. (29th April 2015) - Della Rosa, Kelly A.; Fellman, Danielle; DeBiase, Cortney; DeQuinzio, Jaime A.; Taylor, Bridget A.
<x xml:space="preserve">Abstract</x> A reversal design was used to examine the effects of a differential reinforcement of other behavior (DRO) procedure and the presence of a stimulus (i.e., a bracelet), conditioned via discrimination training, on reducing socially maintained non‐contextual vocalizations in an adolescent girl with autism. Initially, a functional analysis determined that non‐contextual vocalizations were maintained by social attention. Then, discrimination training was used to establish the presence of the bracelet as a discriminative stimulus for the absence of vocalizations. Specifically, when the bracelet was on, non‐contextual vocalizations were interrupted, and edible reinforcement was provided for the absence of vocalizations. When the bracelet was off, vocalizations were not interrupted and the teacher provided social attention to the participant (i.e., reciprocated conversation with the participant about the topic). During intervention, a DRO procedure was used. The participant was presented with the bracelet, a timer set for a specified interval, and the instruction to work quietly. If vocalizations did not occur for the entire duration of the interval, the bracelet was removed and the learner was given the opportunity to engage in vocalizations. The DRO interval was systematically increased throughout the intervention. Results are discussed in terms of discrimination training as an effective addition to differential reinforcement procedure. Copyright © 2015 John Wiley & Sons, Ltd.